1985
DOI: 10.1128/aem.49.5.1276-1281.1985
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella infections in a marsupial, the quokka (Setonix brachyurus), in relation to seasonal changes in condition and environmental stress

Abstract: An unusual abundance of Salmonella infections was studied in an island population of a wild marsupial, the quokka (Setonix brachyurus), which experiences starvation in summer associated with significant mortality. The frequency of infections was found to vary seasonally over most parts of the island, with high infection rates (70 to 100%) in summer and low infection rates (0 to 30%) in winter. In some samples, there was an average of as many as two isolations per animal, and up to five isolations were made fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…The prevalence of fecal Salmonella in this study is markedly lower than reported levels of infection in quokkas (S. brachyurus) on Rottnest Island, which peaks as high as 70-100% in summer (Iveson and Bradshaw, 1973;Hart et al, 1985). This finding can possibly be attributed to the increased exposure of quokkas to people and their waste products within a closed island population.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…The prevalence of fecal Salmonella in this study is markedly lower than reported levels of infection in quokkas (S. brachyurus) on Rottnest Island, which peaks as high as 70-100% in summer (Iveson and Bradshaw, 1973;Hart et al, 1985). This finding can possibly be attributed to the increased exposure of quokkas to people and their waste products within a closed island population.…”
Section: Discussioncontrasting
confidence: 76%
“…This finding can possibly be attributed to the increased exposure of quokkas to people and their waste products within a closed island population. During summer, when food availability is low and digestive physiology is disrupted, quokkas scavenge through food scraps left by tourists, increasing the risk of infection with Salmonella (Samuel, 1983;Hart et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors -together with the presence of young animals -may combine to cause overt salmonellosis. A reduction in the level of nutrition was responsible for an increased shedding rate in quokkas (Setonix brachyurus) in Western Australia (19). With the current profusion of free-ranging macropods in wildlife parks, the general public is coming into closer contact with carrier animals and some zoonotic potential therefore exists.…”
Section: Macropodsmentioning
confidence: 99%